A case study on Persian Geometric Islimis for furniture design / Mahdieh Mirmoezi - Mirmoezi, Mahdieh (2014)
These days, many countries are more concerned about culture where the traditions and thought exist and are putting spurs to the promotion of more value-added cultural industries, the development of individual cultural contents and products, and the growth of the national images and profits. In this research project, it has been tried to develop a cultural product based on ancient traditional culture and heritage in order to have their strength and values approved by and spread to the world. With their primitive and beautiful visual arts, Persia's original cultures present great possibility for developing design value and becoming accepted in the global market. Facts show very high projections for Persian local cultures to become important cultural elements for future design purposes. The intention of this research is to discover the meaning of cultural features from Persian original cultures and to rediscover their cultural values. This research attempts to show how, by developing the unique meaning and images of these cultural features and by helping new methods of design, they can be changed into modern products that satisfy the desires of the modern customer market. The specific cultural feature chosen for this study was the Geometric Islimi pattern on decorative tiles of Safavid architectures. The study focuses on analysing the appearance of the chosen samples, their spiritual meaning, and the symbolic cultural values hidden in them. Finally, this research improves a cultural product design model that is helping designers designing a successful cultural product. The results presented suggest the experience of design and culture in the design process. This study is focuses on Persian Geometric Islimis in decorative architectural patterns during the Safavid era, and recognizing the physical and spiritual values of those designs. Those cultural values will be guidelines for furniture design that represent Persian culture.